A new species of Liolaemus from central steppes of Chubut, Patagonia Argentina (Reptilia: Iguania: Iguanidae) - Scolaro, José A.; Cei, José M. (Zootaxa, 2006)
A new Liolaemus species related to “Liolaemus kingii” complex of Patagonian species, is described. It lives at about 800 m of altitude in a sandy habitat near to Somuncurá plateau. The new species and the closely related L. somuncurae are morphologically compared, and its distribution and natural history are pointed out.